Gpr176 is a Gz-linked orphan G-protein-coupled receptor that sets the pace of circadian behaviour - Masao Doi (Nature Portfolio, 2016)
The suprachiasmatic nucleus (SCN) is the central regulator of circadian rhythms. Here the authors identify mouse Gpr176 as a pace modulator of this circadian clock and characterize its mode of action as coupling to Gz rather than Gi subunits.